How Climate Adaptation Can Reduce Poverty and Promote Gender Equality - Roy, Shalini; Gilligan, Daniel O.; Abhilashi, Raashe; Nesbitt-Ahmed, Zahrah; Goldberg, Mark Leon; Solozano, Ana (CGIAR, 2023)
This episode was recorded as a live taping of the podcast, produced in partnership with CGIAR, a global research partnership for a food-secure future dedicated to transforming food, land, and water systems in a climate crisis. Global Dispatches and CGIAR are partnering on a series of episodes about the nexus between climate and security. In this episode, we host a panel discussion with four experts who discuss the interplay between climate adaptation on the one hand, and poverty reduction and gender equality on the other. They offer expert insights on how climate adaptation can enhance social protection – and vise versa, how social protection measures can support climate adaptation.